Cultural Memory and Postcolonial Perspectives in Modern Indonesian Novels - Nur Ali Yasin; Maulana Anwar; Abi Umaroh; Sahal Hanafi (Journal of Literary and Linguistic Research, 2026)
This research examines cultural memory and postcolonial perspectives in modern Indonesian novels through a non-empirical qualitative research design grounded in close reading and thematic-interpretive analysis. Drawing on cultural memory studies and postcolonial theory, the study investigates how Indonesian fiction constructs remembrance as a contested narrative process shaped by trauma, ecological imaginaries, diasporic displacement, and institutional heritage politics. The findings indicate that novels function as mnemonic spaces where colonial violence persists through fragmented temporalities, familial transmission of trauma, and symbolic struggles over monuments, museums, and cultural routes. Literary representations complicate civic and state-centered historiographies by foregrounding silenced indigenous voices and ethical tensions surrounding the narration of historical suffering. The analysis further demonstrates that cultural memory circulates not only through institutional infrastructures but also through vernacular practices such as ritual continuity and food heritage, expanding the scope of postcolonial remembrance beyond official commemoration. By positioning Indonesian novels as counter-archives of colonial afterlives, this study contributes theoretically to debates on collective memory and methodologically to interpretive approaches in postcolonial literary criticism.